LEADERSHIP TRANSFORMATION IN ISLAMIC EDUCATION MANAGEMENT: SYSTEMATIC LITERATURE REVIEW: TRANSFORMASI KEPEMIMPINAN DALAM MANAJEMEN PENDIDIKAN ISLAM: SISTEMATIC LITERATURE REVIEW - Reni Suwenti; Eti Kurniawati; Een Masdariah; Enung Nugraha; Naf'an Tarihoran (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The digital era and globalization have created complex challenges for Islamic education systems that demand a fundamental reorientation in educational leadership paradigms. Bass and Avolio's transformational leadership theory provides a relevant conceptual framework for understanding leadership evolution in the face of these systemic changes. Leadership transformation in Islamic education management is a complex phenomenon that is rapidly developing in the digital era. This research aims to explore the dynamics of educational leadership change through a systematic literature review method by analyzing current research publications. The study employs a qualitative approach by examining 12 research articles focusing on leadership transformation in various Islamic educational institutions in Indonesia. The research findings reveal four main dimensions of leadership transformation: (1) digitalization of educational administration, (2) shift in leadership style from conventional to transformational, (3) development of educator competencies, and (4) integration of technology in the learning process. The findings highlight that contemporary Islamic education leaders face significant challenges in adapting digital technology, developing human resources, and creating innovative learning environments while maintaining authentic Islamic values. The transformation demonstrates positive impacts on improving learning quality and organizational effectiveness, although cultural resistance, digital literacy gaps, and limited financial resources remain significant obstacles. This research provides theoretical contributions in understanding contemporary educational leadership dynamics and offers practical implications for Islamic education management in the digital era. The research recommends the development of a more systematic adaptive-integrative leadership model, the establishment of technology-based continuous leadership training programs, and increased investment in digital infrastructure in Islamic educational institutions. Future research should conduct longitudinal studies with mixed-methods approaches, geographical expansion to other Muslim countries, and development of valid measurement instruments for leadership transformation effectiveness to achieve a more comprehensive understanding of Islamic educational leadership dynamics in the digital era